FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI KOTA TOMOHON - Maria F. Talokon; Theodora M. Katiandago; Gene H. Kapantow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
This study aimed to analyze factors that influenced the unemployment rate in Tomohon City. The factors included in the analysis were population growth, regional wage growth and GRDP growth. The data used were secondary data from 2008 to 2017 published by BPS (Statistics Indonesia). The analytical method used was Regression Analysis. The results showed that from the three variables analyzed only the regional wage growth had a significant effect on the unemployment rate in Tomohon. The higher the regional wage growth, the lower the unemployment rate. The population growth rate had a positive but not significant effect on the unemployment rate. The GRDP growth had a negative but not significant effect.Keywords: Unemployment rate, Population growth, GRDP, Tomohon